1998
DOI: 10.1046/j.1460-9568.1998.00203.x
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of dopamine-induced cAMP formation by group I metabotropic glutamate receptors via protein kinase C in cultured striatal neurons

Abstract: Metabotropic glutamate receptors have been shown to potentiate the cyclic adenosine monophosphate (cAMP) formation induced by activation of several receptors linked to adenylyl cyclase via Gs-protein. Here we show that, in primary cultures of striatal neurons, group I metabotropic receptors potentiate the cAMP formation induced by activation of D1-like dopamine receptors. Reverse transcription associated with polymerase chain reaction revealed that mGluR5, mGluR3, mGluR4 and mGluR7 are present in striatal cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 26 publications
(55 reference statements)
4
20
0
Order By: Relevance
“…Moreover, both D1R and NMDA receptors in the accumbens appear critical for the early consolidation of appetitive Pavlovian memories (Dalley et al, 2005). These reports are particularly relevant in the context of our current findings, given the close interactions between mGluR5 and D1R (Paolillo et al, 1998;Voulalas et al, 2005;Schotanus and Chergui, 2008) and NMDA receptors (Pisani et al, 2001;Mao and Wang, 2002;Choe et al, 2006) in the striatum. Thus, it is possible that impaired incentive learning and relapse-like behaviors in mGluR5 KD-D1 mice were due, in part, to changes in striatal D1R and NMDA receptor function as a consequence of mGluR5 loss.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Moreover, both D1R and NMDA receptors in the accumbens appear critical for the early consolidation of appetitive Pavlovian memories (Dalley et al, 2005). These reports are particularly relevant in the context of our current findings, given the close interactions between mGluR5 and D1R (Paolillo et al, 1998;Voulalas et al, 2005;Schotanus and Chergui, 2008) and NMDA receptors (Pisani et al, 2001;Mao and Wang, 2002;Choe et al, 2006) in the striatum. Thus, it is possible that impaired incentive learning and relapse-like behaviors in mGluR5 KD-D1 mice were due, in part, to changes in striatal D1R and NMDA receptor function as a consequence of mGluR5 loss.…”
Section: Discussionsupporting
confidence: 60%
“…Although mGluR5 is densely expressed on both D1-and D2-MSN populations (Tallaksen-Greene et al, 1998), converging lines of research would suggest that mGluR5 located specifically on D1-MSNs is ideally positioned to influence associative reward-learning processes that may underpin relapse triggered by drug-paired stimuli. First, there is evidence that striatal dopamine D1 receptors (D1R) play a critical role in both the consolidation of associative reward-learning memories (Dalley et al, 2005) and many of the long-term effects of addictive drugs (Anderson and Pierce, 2005) and second, mGluR5 appears to interact closely with D1Rs to regulate striatal neurotransmission (Paolillo et al, 1998;Voulalas et al, 2005;Schotanus and Chergui, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…This model is in contrast with what was found by other authors in PC12 cells (16), in which depolarization-induced Ca 2ϩ entry activates the ERK pathway via a two-step mechanism involving first PKA and then Rap1. In a previous study (33) and in experiments not reported here, we found that, in cultured striatal neurons, Ca 2ϩ entry induced by a Ca 2ϩ ionophore or by depolarization inhibits cAMP formation, probably interacting with the Ca 2ϩ -inhibitable type V adenylyl cyclase isoform, which is abundantly expressed in these neurons (18).…”
Section: Discussionsupporting
confidence: 58%
“…Trizol, fetal bovine serum, horse serum, and all reagents for cell cultures were from Life Technologies, Inc. The protein kinases inhibitors N- [2-(p- Cell Culture-Primary cultures were obtained as previously described (18). Briefly, striata of 16 -17-day-old Harlan Sprague-Dawley rat embryos were dissected and incubated with papain.…”
Section: Methodsmentioning
confidence: 99%
“…Although molecular details are lacking, a number of published reports provide evidence suggesting that significant interactions occur between pathways activated by mGluR and dopamine receptors in the striatum (Berke et al, 1998;Paolillo et al, 1998;Calabresi et al, 1999;Hanania and Johnson, 1999). In primary cultures derived from E18 striatum, we found that stimulation of neurons with 10 M DHPG together with 10 M R(ϩ)SKF38393 enhanced ERK2 phosphorylation (see Fig.…”
Section: Dr1/5 Enhances Erk2 Phosphorylation By Metabotropic Glutamatmentioning
confidence: 78%